High serum LDH and liver metastases are the dominant predictors of primary cancer resistance to anti-PD(L)1 immunotherapy. (December 2022) - Dercle, Laurent; Ammari, Samy; Roblin, Elvire; Bigorgne, Amelie; Champiat, Stéphane; Taihi, Lokmane; Plaian, Athèna; Hans, Sophie; Lakiss, Sara; Tselikas, Lambros; Rouanne, Mathieu; Deutsch, Eric; et al.
Abstract: Aim: Anti-PD-(L)1 immunotherapies improve survival in multiple cancers but remain ineffective for most patients. We applied machine-learning algorithms and multivariate analyses on baseline medical data to estimate their relative impact on overall survival (OS) upon anti-PD-(L)1 monotherapies. Method: This prognostic/predictive study retrospectively analysed 33 baseline routine medical variables derived from computed tomography (CT) images, clinical and biological meta-data. 695 patients with a diagnosis of advanced cancer were treated in prospective clinical trials in a single tertiary cancer centre in 3 cohorts including systemic anti-PD-(L)1 (251, 235 patients) versus other systemic therapies (209 patients). A random forest model combined variables to identify the combination (signature) which best estimated OS in patients treated with immunotherapy. The performance for estimating OS [95%CI] was measured using Kaplan–Meier Analysis and Log–Rank test. Results: Elevated serum lactate dehydrogenase (LDH hi ) and presence of liver metastases (LM+) were dominant and independent predictors of short OS in independent cohorts of melanoma and non-melanoma solid tumours. Overall, LDH hi LM+ patients treated with anti-PD-(L)1 monotherapy had a poorer outcome (median OS: 3.1[2.4–7.8] months]) compared to LDH low LM-patients (median OS: 15.3[8.9-NA] months; P < 0.0001). The OS of LDH low LM-patients treated with immunotherapy was 28.8[17.9-NA] months (vs 13.1[10.8–18.5], P = 0.02) in the overall population and 30.3[19.93-NA] months (vs 14.1[8.69-NA], P = 0.0013) in patients with melanoma. Conclusion: LDH hi LM+ status identifies patients who shall not benefit from anti-PD-(L)1 monotherapy. It could be used in clinical trials to stratify patients and eventually address this specific medical need. Highlights: A baseline machine learning-derived signature predicted survival on immunotherapy. LDH hi (elevated serum LDH) and LM+ (liver metastasis) forecasted short survival. LDH low LM-forecasted longer survival with immunotherapy than other systemic therapies. LDH LM status could guide clinical decision making for advanced cancer patients.